Sex difference in synaptic plasticity in the anterior cingulate cortex of adult mice - Ren-Hao Liu; Man Xue; Xu-Hui Li; Min Zhuo (Molecular Brain, 2020)
Abstract Sex differences in certain types of pain sensitivity and emotional responses have been previously reported. Synaptic plasticity is a key cellular mechanism for pain perception and emotional regulation, including long-term potentiation (LTP) and long-term depression (LTD). However, it is unclear whether there is a sex difference at synaptic level. Recent studies indicate that excitatory transmission and plasticity in the anterior cingulate cortex (ACC) are critical in chronic pain and pain related emotional responses. In the present study, we used 64-channel multielectrode (MED64) system to record synaptic plasticity in the ACC of male and female adult mice. We found that there was no significant difference in theta-burst stimulation (TBS)-induced LTP between female and male mice. Furthermore, the recruitment of inactive channels was also not different. For LTD, we found that LTD was greater in slices of ACC in male mice than female mice. Our results demonstrate that LTP in the ACC does not show any sex-related difference.